Membangun Definisi Genetis Kubus Melalui Distorsi dan Manipulasi Objek Spasial - Fiantika, Feny Rita; Budayasa, I Ketut; Lukito, Agung (Jurnal Elemen, 2017)
Geometry is one of school material subject which close with our daily activities. They used geometry form concept to interior and exterior design. The closeness between geometry content and daily activities encourage author to explore how is spatial thinking elementary student. Two kinds of representations are internal representation and external representation. Representation internal include perception, distortion or abstraction and relationships between objects, external representation reveal the product of thought to image, words, table, concrete object, or mathematic symbols used to understand yourself and others.Transformation is representation component. Transformation needs object to operate it, and representation needs transformation to create representation. Transformation is tool to descript representations.Subject of the research is elementary school students grade 5th, the researcher gives them a problem of geometry object 2 dimensions to 3 dimensions The research findings are the subject be able to construct a genetic definition of the cube by using analogical thinking in the preparation of the definition.